Overview of APEX Project Results - Prech, Lubomir; Ruzhin, Yuri Y.; Dokukin, Vladimir S.; Nemecek, Zdenek; Safrankova, Jana (Frontiers in Astronomy and Space Sciences, 2018)
The APEX mother-daughter project (Active Plasma EXperiments) was launched into an elliptical polar orbit (440 –-- 3080 km) in December 1991. It consisted of the main Russian Interkosmos--25 (IK--25) satellite and the Czech MAGION--3 subsatellite, both with international scientific payloads. The mission used intensive modulated electron beam emissions and xenon plasma or neutral releases from the main satellite for studies of dynamic processes in the magnetosphere and upper ionosphere. Its main scientific objectives were to simulate an artificial aurora and to study optical and radio emissions from the aurora region, and to investigate the dynamics and relaxation of modulated electron and plasma jets, artificially injected into the ionospheric plasma. The experiments studied the Critical Ionization Velocity phenomenon and a diamagnetic cavity formation during the xenon releases, local and distant effects of the electron beam injection, spacecraft charging and potential balance, and plasma-wave interactions during the artificial emissions. Attempts were performed to utilize the modulated electron beam as an active transmitting antenna in the space. The theory of ballistic wave propagation across plasma barrier was tested in a joint active experiment with the Dushanbe ionospheric heater facility. In the paper, we give a short overview of the IK--25/MAGION--3 scientific instrumentation and methodology of experiments with artificial beam injections and we provide a review of the main APEX active experiments results, many of which have been published only in the Russian language so far. From a historical 25-years-long perspective, we try to put the results of the APEX experiments into the context of other active experiments in the space plasma.